Role of health literacy in an information society - CHRÁSKOVÁ, Marie (Journal of Education, Technology and Computer Science, 2014)
The paper addresses the role of health literacy in a contemporary information society. Specifically, the paper defines the concept of health literacy, not only from a WHO perspective but also according to various authors. The paper also analyses the factors influencing the level of health literacy in a population. One of the conclusions of the paper is the need for continuous improvement of people’s health literacy, which nowadays cannot do without institutional and lifelong learning and also efficient use of information technologies.